A micro-CT analysis of murine lung recruitment in bleomycin-induced lung injury - Shofer, Scott (American Physiological Society, 2008)
The effects of lung injury on pulmonary recruitment are incompletely understood. X-ray computed tomography (CT) has been a valuable tool in assessing changes in recruitment during lung injury. With the development of preclinical CT scanners designed for thoracic imaging in rodents, it is possible to acquire high-resolution images during the evolution of a pulmonary injury in living mice. We quantitatively assessed changes in recruitment caused by intratracheal bleomycin at 1 and 3 wk after administration using micro-CT in 129S6/SvEvTac mice. Twenty female mice were administered 2.5 U of bleomycin or saline and imaged with micro-CT at end inspiration and end expiration. Mice were extubated and allowed to recover from anesthesia and then reevaluated in vivo for quasi-static compliance measurements, followed by harvesting of the lungs for collagen analysis and histology. CT images were converted to histograms and analyzed for mean lung attenuation (MLA). MLA was significantly greater for bleomycin-exposed mice at week 1 for both inspiration (P < 0.0047) and exhalation (P < 0.0377) but was not significantly different for week 3 bleomycin-exposed mice. However, week 3 bleomycin-exposed mice did display significant increases in MLA shift from expiration to inspiration compared with either group of control mice (P < 0.005), suggesting increased lung recruitment at this time point. Week 1 bleomycin-exposed mice displayed normal shifts in MLA with inspiration, suggesting normal lung recruitment despite significant radiographic and histological changes. Lung alveolar recruitment is preserved in a mouse model of bleomycin-induced parenchymal injury despite significant changes in radiographic and physiological parameters.